Early-life supplementation of bovine Milk Osteopontin prevents adult obesity by elevating succinic acid and acting through its receptor GPR91 - Lan Liu; Yilei Lao; Zixin Zhang; Chenming Lin; Yeqing Zhou; Zhimin Zhang; Bo Lönnerdal; Zhijian Cai; Junfen Fu (Food Research International, 2026)

Corrigendum to “Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study” [Environ. Res., 263(Pt 1), 2024, 120038] - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2026)

Associations of PFOA and PFOS exposure with liver injury: Evidence from Two Population Studies and integrative adverse outcome pathway analysis - Yingqian You; Xin Guan; Hui Zhao; Tianhao Wu; Chenming Wang; Yang Xiao; Yuhan Zhou; Shiru Hong; Ye Fu; Meian He; Huan Guo (Environmental Pollution, 2025)

Benzo[a]pyrene exposure and incident risks of digestive system cancers: Insights from nested case-control studies and adverse outcome pathway network analysis - Hui Zhao; Yang Xiao; Ye Fu; Xin Guan; Ming Fu; Chenming Wang; Yuhan Zhou; Shiru Hong; Yingqian You; Yuxi Wang; Shengli Chen; Yichi Zhang; et al. (Journal of Hazardous Materials, 2025)

A laboratory study on wave Attenuation by oyster reefs-mangrove system - Beihan Jiang; Chenming Fu; Tuofu You; Yuanmin Sun; Xiaohe Lai; Feng Cai; Zhaoyang Hu; Xinqiang Wang; Liang Chen; Yitan Lin; Chunling Pan (Geo-Marine Letters, 2025)

Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2024)

Mitochondrial DNA copy number mediated the associations between perfluoroalkyl substances and breast cancer incidence: A prospective case-cohort study - Yue Feng; Yingqian You; Mengying Li; Xin Guan; Ming Fu; Chenming Wang; Yang Xiao; Meian He; Huan Guo (Science of The Total Environment, 2024)

Particulate matter pollution, polygenic risk score and mosaic loss of chromosome Y in middle-aged and older men from the Dongfeng-Tongji cohort study - Xin Guan; Xia Meng; Guorong Zhong; Zirui Zhang; Chenming Wang; Yang Xiao; Ming Fu; Hui Zhao; Yuhan Zhou; Shiru Hong; Xuedan Xu; Yansen Bai; et al. (Journal of Hazardous Materials, 2024)

The interaction effects of zinc and polygenic risk score with benzo[a]pyrene exposure on lung cancer risk: A prospective case-cohort study among Chinese populations - Ming Fu; Hua Meng; Minghui Jiang; Ziwei Zhu; Xin Guan; Yansen Bai; Chenming Wang; Yuhan Zhou; Shiru Hong; Yang Xiao; Meian He; Xiaomin Zhang; et al. (Environmental Research, 2024)

DNA methylation aging signatures of multiple metals exposure and their mediation effects in metal-associated mortality: Evidence from the Dongfeng-Tongji cohort study - Chenming Wang; Guorong Zhong; Chenliang Liu; Shiru Hong; Xin Guan; Yang Xiao; Ming Fu; Yuhan Zhou; Yingqian You; Tianhao Wu; Hui Zhao; Yuxi Wang; et al. (Journal of Hazardous Materials, 2024)

Associations between multiple metals exposure and biological aging: Evidence from the Dongfeng-Tongji cohort - Chenming Wang; Shiru Hong; Xin Guan; Yang Xiao; Ming Fu; Hua Meng; Yue Feng; Yuhan Zhou; Qiang Cao; Fangfang Yuan; Chenliang Liu; Guorong Zhong; et al. (Science of The Total Environment, 2023)

Multiple metals exposure and blood mitochondrial DNA copy number: A cross-sectional study from the Dongfeng-Tongji cohort - Ming Fu; Chenming Wang; Shiru Hong; Xin Guan; Hua Meng; Yue Feng; Yang Xiao; Yuhan Zhou; Chenliang Liu; Guorong Zhong; Yingqian You; Tianhao Wu; et al. (Environmental Research, 2023)

Experimental study on the effect of an oyster reef on the nonlinear characteristics of irregular waves - Beihan Jiang; Hui Zhang; Tuofu You; Yuanmin Sun; Chenming Fu; Weijie Liao; Feng Cai (Frontiers in Marine Science, 2022)
As a “marine ecological engineer”, the oyster reefs not only perform important ecological functions, but also reduce the damage caused by waves to protective structures such as seawalls. However, oyster reefs in shallow water change the nonlinear characteristics of waves and affect sediment transport and coastal evolution. Based on Fourier spectrum and analysis of Wavelet Transform, the influence of artificial bag oyster reefs on the energy and nonlinear phase coupling of irregular waves are studied through physical experiment. The results show that oyster reefs have a substantial effect on the energy of primary harmonic, which transfer to higher harmonics through triad interactions, and a considerable reduction in primary harmonic energy and an increase in higher harmonics energy are reflected in the energy spectra. The transmission spectrum behind the oyster reefs shows three peaks at primary, secondary and third harmonics. The bicoherence spectrum indicates that the peaks at secondary and third harmonics mainly result from the self-coupling of the primary harmonics and phase coupling between the primary and secondary harmonics respectively. As the water depth increases, the degree of nonlinear coupling between wave components decreases, which leads to the energy of wave components at different frequencies increases. With increasing top width, the length of the shoaling region increases, and the growth of triad nonlinear interactions are observed in wavelet-based bicoherence spectra, resulting in the spectral peak energy decreasing while the secondary harmonics energy increasing in the spectrum. Finally, the potential application of an ecological system composed by “oyster reefs + mangroves” is discussed. As the effect of water depth on wave energy is much greater than that of top width, in artificial oyster reef construction, it is recommended that keep the oyster reefs non-submerged in terms of wave dissipation. Further studies should take the dynamic growth effect of oyster reefs into account.